Thyroidal Effects of Di-(2-Ethylhexyl) Phthalate in Rats of Different Selenium Status - Erkekoglu, Pinar; Giray, Belma Kocer; Kizilgun, Murat; Hininger-Favier, Isabelle; Rachidi, Walid; Roussel, Anne-Marie; Favier, Alain; Hincal, Filiz (BEGELL HOUSE INC, 2012)
This study was designed to investigate the effects of di-(2-ethylhexyl) phthalate (DEHP) on thyroid hormone levels and oxidant/antioxidant parameters in the rat and to evaluate the effects of selenium status. Selenium deficiency was produced by feeding 3-week-old Sprague-Dawley rats with <0.05 mg selenium/kg body weight for 5 weeks, and the supplementation group received a diet of 1 mg selenium/kg body weight DEHP-treated groups received the compound at a dose of 1000 mg/kg by gavage during the last 10 days of the feeding period. Levels of thyroid hormone levels as well as selenoenzyme (glutathione peroxidase 1, thioredoxin reductase), catalase, and superoxide dismutase (SOD) activity and thiobarbituric acid reactive substance (TBARS) were measured. Total thyroxine (TT4) levels decreased significantly with DEHP exposure (similar to 25%), whereas TT3 level was not altered. The TT4 lowering effect of DEHP exposure was not affected by selenium deficiency but was observed when animals exposed to DEHP received a selenium supplement DEHP was found to alter the antioxidant status and induce oxidative stress in rat thyroid by increasing SOD activity (similar to 30%) and TBARS levels (similar to 35%). The effects of DEHP were much more pronounced in selenium-deficient rats, as evidenced by significant increases in SOD activity (similar to 65%) and TBARS levels (similar to 55%) compared with the control levels. Thus, these results show the thyroid-disrupting effect of DEHP in rats and protection by selenium.
Keywords: di-(2-ethylhexyl) phthalate (DEHP); selenium deficiency; selenium supplementation; thyroid; lipid peroxidation; ENDOCRINE-DISRUPTING CHEMICALS; PEROXISOME PROLIFERATORS; URINARY PHTHALATE; DI(2-ETHYLHEXYL) PHTHALATE; ENVIRONMENTAL CHEMICALS; GLUTATHIONE-PEROXIDASE; METABOLITES; HEALTH; MALONDIALDEHYDE; INDUCTION; Toxicology